The Impact of Cultural Globalization on Growth - Leitão, Nuno Carlos (Asian Journal of Empirical Research, 2012)
This paper investigates the relationship between cultural globalization and economic growthin case of Portuguese over the period of 1995-2008 uisng panel data. Our emoirical eivdence reveals that the initial GDP per capita is negatively correlated with economic growth. This paper shows that international trade and cultural globalization promote economic growth.